Wooh! - Matt Thomson (Symphony in the Flint Hills, 2011)
A vision of the early history of Wabunsee County capturing an interaction with a band of Pottawatomie Native Americans.
Keywords: winter; storm; 1861; Native Americans; Indians; Fix; Wabunsee County; Pioneer; early days; Western Border; Pottawatomie; Pawnee; ponies; buffalo; mill